Recent trends in consumption in Japan and the other Group of Seven (G7) countries - Charles Yuji Horioka (Osaka University, Institute of Social and Economic Research (ISER), 2012)
In this paper, we present data on recent trends in private consumption and in possible determinants of private consumption (such as GDP, household incomes, household saving rates, household wealth, and employment conditions) in the Group of Seven (G7) countries and find that there has been significant variability among the G7 countries not only in their private consumption growth rates but also in the determinants of private consumption growth during the 2002-07 period. With respect to Japan, we find that private consumption has been relatively stagnant during the 2002-07 period and that the stagnation of private consumption has been due to the stagnation of household income and of household wealth and the relative stability of the household saving rate.
Keywords: D12; E21; E60; J64; 330; consumption; private consumption; GDP; economic growth; households; saving; wealth; employment conditions; unemployment rates; Group of 7 (G7); Japan; Gesamtwirtschaftlicher Konsum; Nationaleinkommen; Sparen; Haushaltseinkommen; Arbeitslosigkeit; G8-Staaten; Japan